Evaluating agroclimatic constraints and yield gaps for winter oilseed rape (Brassica napus L.) – A case study - Zhi Zhang (Nature Portfolio, 2017)
Abstract Evaluating the effects of agroclimatic constraints on winter oilseed rape (WOSR) yield can facilitate the development of agricultural mitigation and adaptation strategies. In this study, we investigated the relationship between the WOSR yield and agroclimatic factors using the yield data collected from Agricultural Yearbook and field experimental sites, and the climate dataset from the meteorological stations in Hubei province, China. Five agroclimatic indicators during WOSR growth, such as ≥0 °C accumulated temperature (AT-0), overwintering days (OWD), precipitation (P), precipitation at an earlier stage (EP) and sunshine hours (S), were extracted from twelve agroclimatic indices. The attainable yield for the five yield-limiting factors ranged from 2638 kg ha−1 (EP) to 3089 kg ha−1 (AT-0). Farmers (Y farm ) and local agronomists (Y exp ) have achieved 63% and 86% of the attainable yield (Y att ), respectively. The contribution of optimum fertilization to narrow the yield gap (NY exp ) was 52% for the factor P, which was remarkably lower than the mean value (63%). Overall, the precipitation was the crucial yield-limiting agroclimatic factor, and restricted the effect of optimizing fertilization. The integrated data suggest that agricultural strategies of mitigation and adaptation to climatic variability based on different agroclimatic factors are essential for improving the crop yield.